THE SCIENCE OF COMMUNICATION AND NEGOTIATION IN MEDIATION - ELENA NEDELCU (Challenges of the Knowledge Society)
The present study proposes to contribute in clarifying a subject of great actuality and social importance: why does the contemporary society need such mediation and mediators and what are the psycho-social premises of making the process of mediaton more efficient. In the first part, this study keeps the track of identifying the connections and the distinctions between communication-negotiation and mediation. The intercession carries forward with the analysis of the communicational and negotiative abilities of the mediator – premises of efficient mediation. The final part consists in an argument towards the imperative need of mediation felt by the contemporary society at all its levels.